Determinants of international tourists’ mall patronage in the Klang Valley, Malaysia - Asadifard, Mozhdeh (2019)
The objective of economic policy is economic growth and policymakers have a particular interest in those industries that improve economic growth. The tourism industry is one of those industries which have a long-term impact on economic growth. In Malaysia, tourism offers a primary influence on economic development, profiting from different categories, explicitly shopping. Moreover, shopping has considered as an essential part of each tourist trip. Therefore, investigating the avid research which examines the tourist shopping behaviour during the travel time is avoidable. The premise of this research is that international tourist shopping differs from the usual daily shopping; the demands of international tourists are distinctive during the travel time. As such empirical studies to recognise the diverse types of international tourists’ behaviours are significant for the theory and practice. Even though much has been done to examine the different aspects of shopping tourism, none has related planned and impulsive behaviour of international tourist to mall patronage. Especially in Malaysia, the study of global tourist mall patronage behaviour is in an early stage. Applying planned behaviour theory and supported by Stimulus-Organism-Response model, this research endeavours to investigate the antecedents’ precursors and results of international tourist shopping planned and impulsive behaviour in well-recognised shopping malls in Klang Valley, Malaysia. This study employed a self-administered questionnaire to conveniently gather data from 200 international tourists in four tourist-destination shopping centres located in Klang Valley, Malaysia. A structural equation modelling software was used to identify the direct and mediating effects hypotheses. Bootstrapping techniques were applied to examine the mediating effect.Outcomes were not able to advocate relations between the two planned behaviour precursors (utilitarian attitude and subjective norm) and mall patronage behaviour. Only perceived behavioural control of planned behaviour was affirmed to have a meaningful positive connection with mall patronage behaviour. Besides, environmental factors antecedent of impulsive behaviour had also a significant positive relationship with mall patronage behaviour. Patronage intention was also revealed to completely mediate how perceived behavioural control and patronage behaviour were related. On the other hand, the full mediation of patronage intention in the association between perceived behavioural control and patronage behaviour identified that perceived behavioural control to tourism can only explain tourist patronage behaviour with the role of tourist patronage intention. Findings confirmed that tourist mall patronage behaviour is associated with both types of planned and impulsive reactions. This study provides several theoretical contributions and additional perceptions into the antecedents’ precursors and outcomes of mall patronage behaviour in Malaysia, a destination considered as highly promising for shopping tourism. As a final point, the findings support the study’s research proposition and offer some exciting implications for academics and practitioners. The current study advances our knowledge in the area of shopping tourism by testing the prediction of the planned behaviour, impulsive behaviour and experiential consumption on international tourists’ patronage intent to visit and shop in the mall.